Rancangan Teknis Stockpile 2 Di PT Bukit Asam Tbk, Unit Pelabuhan Tarahan - Lampung - Merja Arta; Ansosry Ansosry (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. PT Bukit Asam Tbk, is one of the largest coal mining companies in Indonesia. In distributing coal to consumers, PT Bukit Asam Tbk has supporting facilities namely Tarahan Port in Lampung and Kertapati Pier in Palembang. Coal production is increasing every year and in 2023 PT Bukit Asam Tbk plans 45 million tons of coal shipments to Tarahan Port and will require a large and maximum stockpile of capacity to meet the needs of coal shipping from Tanjung Enim. The actualization of the evaluation of the stockpile 2 capacity was 189,213.84 tons of the planned 250,000 tons of coal capacity. If there is a rain of coal spilling into the open channel (drainage) until it covers around the stockpile 2 which has a length of 625 m. This causes the formation of acid water in the bottom of the stockpile and causes flooding around it. So recommendations were made to minimize the occurrence of landslides and reduce the use of excavators for cleaning drainage.Keywords: Stockpile, Drainage,Capacity, Excavator, Coal